Mudra’s Contribution towards Weaker Sections (SC/ST/OBCs) (Financing of SC/ST/OBCs through MUDRA since its Establishment): Addressing the Credit Needs of Weaker Sections: MUDRA's Impact on SC/ST/OBCs (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Government of India firmly believes that development has to generate inclusive growth. Large corporate and business entities have a crucial role in economic development. These large entities has to be complemented by informal sector enterprises which generate maximum employment. There are some 5.77 croresmall business units mostly individual proprietorship, in manufacturing, trading or service sector. 62 per cent of these are owned by SCSTOBCs. These bottom of the pyramid and hard-working entrepreneurs find difficulties to access formal systems of credit. To resolve this problem Government of Indiacreate a Micro Units Development Refinance Agency (MUDRA) Bank. MUDRA Bank will refinance Micro-Finance Institutions through Pradhan Mantri Mudra Yojana. In lending, priority will be given to SCSTOBCs. These measures will greatly increase the confidence of young, educated or skilled workers to aspire to become first generation entrepreneurs and existing small businesses can able to expand their activities. In this paper an attempt has been made to find out contribution of MUDRA towards SCSTOBCs. Findings reveal that half of the beneficiaries’ belongs to financially weaker segment comprising of SCs, STs or OBCs.